Treadmill Training Effect on the Myokines Content in Skeletal Muscles of Mice With a Metabolic Disorder Model - Zakharova, Anna Nikolaevna; Kironenko, Tatiana Alexandrovna; Milovanova, Kseniia G.; Orlova, A. A.; Dyakova, E. Yu; Kalinnikova Yu, G.; Kabachkova, Anastasia V.; Chibalin, Alexander V.; Kapilevich, Leonid V. (Frontiers in Physiology, 2021)
The effect of treadmill training loads on the content of cytokines in mice skeletal muscles with metabolic disorders induced by a 16 week high fat diet (HFD) was studied. The study included accounting the age and biorhythmological aspects. In the experiment, mice were used at the age of 4 and 32 weeks, by the end of the experiment - respectively 20 and 48 weeks. HFD feeding lasted 16 weeks. Treadmill training were carried out for last 4 weeks 6 times a week, the duration 60 minutes and the speed from 15 to 18 m/min. Three modes of loading were applied. The first subgroup was subjected to stress in the morning hours (light phase); the second subgroup was subjected to stress in the evening hours (dark phase); the third subgroup was subjected to loads in the shift mode. In 20-week-old animals, the exercise effect does not depend on the training regime, however in 48-week-old animals, the decrease in body weight in mice with the shift training regime was more profound. HFD affected muscle myokine levels. The content of all myokines, except for LIF, decreased, while the concentration of CLCX1 decreased only in young animals in response to HFD. The IL-6 content changed most profoundly. These changes were observed in all groups of animals. The changes depended to the greatest extent on the training time scheme. The effect of physical activity on the content of IL-15 in the skeletal muscle tissue was observed mostly in 48-week-old mice. In 20-week-old animals, physical activity led to an increase in the concentration of LIF in muscle tissue when applied under the training during the dark phase or shift training scheme. In the HFD group, this effect was significantly more pronounced. The content of CXCL1 did not change with the use of treadmill training in almost all groups of animals. Physical activity, introduced considering circadian rhythms, is a promising way of influencing metabolic processes both at the cellular and systemic levels, which is important for the search for new ways of correcting metabolic disorders.